2019
DOI: 10.1002/smll.201901566
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Hydrophobized Microparticles for Accelerated Wound Healing after Endoscopic Submucosal Dissection

Abstract: Endoscopic submucosal dissection (ESD) provides strong therapeutic benefits for early gastrointestinal cancer as a minimally invasive treatment. However, there is currently no reliable treatment to prevent scar contracture resulting from ESD which may lead to cicatricial stricture. Herein, a multifunctional colloidal wound dressing to promote tissue regeneration after ESD is demonstrated. This sprayable wound dressing, composed of hydrophobized microparticles, exhibits the multifunctionality necessary for woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…To detect the biological effects of the hydrogel, we further investigated the histological differences in gastric tissues among the 3 groups. Inflammatory cells were selected as an indicator to evaluate whether AA/AA-NHS hydrogels can change the inflammatory response and possibly accelerate the transition from inflammation to the proliferation phase [ 57 ]. The H&E staining results showed that the number of invading inflammatory cells in gastric wounds significantly decreased in AA/AA-NHS10-treated swine compared with PPI-treated and control swine.…”
Section: Resultsmentioning
confidence: 99%
“…To detect the biological effects of the hydrogel, we further investigated the histological differences in gastric tissues among the 3 groups. Inflammatory cells were selected as an indicator to evaluate whether AA/AA-NHS hydrogels can change the inflammatory response and possibly accelerate the transition from inflammation to the proliferation phase [ 57 ]. The H&E staining results showed that the number of invading inflammatory cells in gastric wounds significantly decreased in AA/AA-NHS10-treated swine compared with PPI-treated and control swine.…”
Section: Resultsmentioning
confidence: 99%
“…A multifunctional colloidal dressing was prepared by Nishiguchi et al (2019 ) to accelerate wound healing after ESD ( Figure 6 ). The wound dressing was composed of hydrophobic microparticles (hMPs), which were prepared as follows: gelatin (Gltn), which is produced by the partial hydrolysis of collagen from the organism, was modified with aliphatic aldehyde to synthesize hydrophobically modified Gltn (hm-Gltn), and then, granulation of hm-Gltn was realized using the spray drying method before being formed into dried hMPs by thermal crosslinking route.…”
Section: Biomedical Polymersmentioning
confidence: 99%
“…(B) Hydrophobic colloidal dressings effectively suppressed wound fibrosis after ESD in the swine stomach model. Reproduced from Nishiguchi et al (2019 ). Copyright (2019), with permission from John Wiley and Sons.…”
Section: Biomedical Polymersmentioning
confidence: 99%
“…Biological tissue is a wet, soft material with high water content that forms a hydration layer on the surface, and this requires harsh chemical reactions to anchor materials to tissues, which may elicit inflammatory responses. The use of physical interactions such as hydrogen bonding, van der Waals force, and hydrophobic interaction can enhance adhesion strength without impairing biocompatibility. The leverage of both the chemical cross-linking reactions and physical interactions can maintain the biocompatibility of tissue adhesives.…”
Section: Introductionmentioning
confidence: 99%